The Effect of Finger grip Relaxation on Decreasing Anxiety of Pre-Sectio Caesarea Patients at RSIA Masyita Makassar - Alam, Rizqy Iftitah; Jama, Fatma; Nurlian, Sri (International Journal of Nursing and Health Services (IJNHS), 2022)
Introduction: Finger-grip relaxation was essential to manage emotions and develop emotional intelligence. Finger-grip relaxation helps the body, mind, and spirit to achieve relaxation. Objective: The study aimed to examine the effect of Finger-grip relaxation on decreasing anxiety of pre-section Caesarea patients at RSIA Masyita Makassar. Method: This study used the quasi-experimental study, one group, pre-test - post-test without control design. Ten samples were carried out using the observation sheet. Ten respondents met the inclusion criteria. This study used a pre-experimental one-group pre-test - post-test without control with the intervention sampling technique. Results: The results found that there was a difference in anxiety levels before and after undergoing Finger-grip relaxation with p-value = 0.00 < ? = 0.05. Before undergoing Finger-grip relaxation (pre-test), there were 6 mothers with moderate anxiety, 2 mothers with mild anxiety, and 2 mothers with severe anxiety. After undergoing Finger-grip relaxation (post-test), eight mothers with mild anxiety and 2 mothers with moderate anxiety. Thus, it can be concluded that there was an influence of Finger-grip relaxation in decreasing the anxiety of pre-Sectio Caesarea patients. Recommendation: This study can be used as a source of information, especially in the field of medical-surgical nursing